Analysis of Behavioral Finance Affecting in Investment Decision - Wisnu Yuwono; Nurtia Putri Sari; Novita Lasmawati; Ranny Daniel; Arief Maulana (Cita konsultindo, 2023)
This article is to analyze what factors influence investment decision making. The method used is a systematic review. Information used in scientific articles and reports that are relevant to the research topic. Investment decision making depends on investor behavior factors. Therefore, this study aims to determine the impact of behavioral finance on investment decisions on investment instruments. Herding behavior, market, loss aversion, and overconfidence were selected as behavioral financial factors. It was found that the most influential factors were market and herding. These results can be used by related parties in making investment decisions.